The increasing use of portable computing and communication devices and its impact on the health of EU workers (Luxembourg, 2010)
"This report aims to shed light on the purported effects of portable computing and communication devices (hereafter called portable IT) on the health and safety of those workers that may be using them more frequently. In fact it is believed that this trend, rather than be attenuated, should increase since it is to be expected that, in its various forms and guises, the use of portable IT will become an unavoidable aspect of ever more professions/occupations. The various types of health effects due to portable IT use, both physical and psychological, are covered in the report. In tackling this challenge the report tries also to characterise patterns of portable IT use among those occupations where it is supposedly more typical. Thus, types of work, working patterns, working environments, categories of workers and the possible disruption to personal life that the portability factor may bring about, are all aspects covered. A prediction of how will portable IT use evolve and the associated health problems to be expected is also included. The public of this report are any interested parties such as employers and employee organisations and representatives, policy makers, managers and workers as well as health professionals, all of whom may find in the report interesting and new information that may help them understand the phenomenon better and make more informed choices. Consequently, the report also includes options for management and legislation to try and compensate for the purported negative health effects of portable IT use."